Computer skills and digital media uses among young students in Rio de Janeiro - Duarte, Rosalia; Cazelli, Sibele; Migliora, Rita Peixoto; Coimbra, Carlos Alberto (Education Policy Analysis Archives, 2013)
The main purpose of this paper is provide information relevant for the formulation of new policies for the integration of technology in education from the discussion of research results that analyse computer skills and digital media uses among students (between 12 to 18 years old) from schools in the city of Rio de Janeiro, Brazil. The schools surveyed were selected by a stratified random sample. The questionnaire allowed for statistical measurement of theoretical constructs employing non parametrical item response theory. The schools showed a homogeneous pattern with regard to the frequency of use and the ability of students to perform tasks on the computer. Most students use the computer and the Internet at home. The use of computers in schools is minimal and does not influence the students' ability. Even so, the use of a computer at school positively affects the frequency of use and suggests that schools can play a role in promoting digital inclusion. The availability of media resources at home, how long students have been using a computer and cultural practices during the students’ free time had notable positive correlations with the student’s abilities. The results suggest that the relation between age and abilities in the use of computer and internet was not significant, except in reference to school delays which were related to age and to students’ grades, i.e., the more delayed a student is, the less able he/she will be.